2022
DOI: 10.3389/fmed.2021.790783
|View full text |Cite
|
Sign up to set email alerts
|

The Human Microbiome in Chronic Kidney Disease: A Double-Edged Sword

Abstract: Chronic kidney disease (CKD) is an increasing global health burden. Current treatments for CKD include therapeutics to target factors that contribute to CKD progression, including renin–angiotensin–aldosterone system inhibitors, and drugs to control blood pressure and proteinuria control. Recently, associations between chronic disease processes and the human microbiota and its metabolites have been demonstrated. Dysbiosis—a change in the microbial diversity—has been observed in patients with CKD. The relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 117 publications
0
26
0
Order By: Relevance
“…Patients with end-stage renal disease (ESRD) tend to have an increase in the microbiota producing a variety of harmful metabolites, such as IS, PCS, and TMAO, and a decrease in the microbiota-producing beneficial metabolites, such as short-chain fatty acids (SCFAs) ( 10 ). These harmful bacteria affect the metabolism of the host, disrupt the intestinal barrier, promote the circulation of harmful metabolites through the damaged intestinal barrier, and then contribute to the progression of renal fibrosis and CKD through various mechanisms, such as promoting inflammation and oxidative stress in CKD ( 25 ). Applying DEseq2 algorithm to further explore the differences in gut microbiome, we found that OTUs between NPD and sham were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with end-stage renal disease (ESRD) tend to have an increase in the microbiota producing a variety of harmful metabolites, such as IS, PCS, and TMAO, and a decrease in the microbiota-producing beneficial metabolites, such as short-chain fatty acids (SCFAs) ( 10 ). These harmful bacteria affect the metabolism of the host, disrupt the intestinal barrier, promote the circulation of harmful metabolites through the damaged intestinal barrier, and then contribute to the progression of renal fibrosis and CKD through various mechanisms, such as promoting inflammation and oxidative stress in CKD ( 25 ). Applying DEseq2 algorithm to further explore the differences in gut microbiome, we found that OTUs between NPD and sham were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such metabolites as occludin and claudin 5 could affect the permeability of the blood–brain barrier (BBB) and thus have an effect on the course of neuroinfection [ 32 ]. Unlike in patients suffering from chronic inflammatory maladies [ 33 , 34 ], changes in gut microbial composition were rarely studied in those with acute inflammatory processes. So far, alterations in the intestinal microbiome have been described in patients with acute pancreatitis [ 35 ] and acute myocardial infarction [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota of CKD patients showed an increase in members of the phylum Bacteroidetes and Proteobacteria and a decrease in Lactobacillus , which belongs to the phyla Firmicutes , compared to healthy individuals [ 41 ]. Lower abundance of Lactobacillus is associated with the development of hypertension and linked to adverse outcomes in patients with CKD [ 42 ].…”
Section: Alterations In the Intestinal Microflora In Chronic Kidney D...mentioning
confidence: 99%
“…In CKD patients, Bifidobacterium from the phyla Actinobacteria was depleted and supplementing Bifidobacterium in CKD specific diets reduced serum creatinine, urea nitrogen, and p-cresyl sulfate, demonstrating its role in reducing the accumulation of these uremic toxins [ 51 ]. Patients with advanced stages of CKD had increased numbers of Eggerthella lenta from the phyla Actinobacteria , Fusobacterium nucleatum from the phyla Fusobacteriota , and Alistipes shahii from the phyla Bacteroidetes [ 42 ].…”
Section: Alterations In the Intestinal Microflora In Chronic Kidney D...mentioning
confidence: 99%